Assessment of characteristics and exposure to vulnerable factors for drug use among male illicit drug users in Sri Lanka: A multicenter cross-sectional study - Nuwan Darshana; Champa Jayalakshmie Wijesinghe; P Vijitha De Silva (Wolters Kluwer Medknow Publications, 2022)
Background: Illicit drug use has become a significant public health problem in Sri Lanka. This study was conducted to assess characteristics and exposure to vulnerable factors for drug use among institutionalized male drug users. Methodology: A cross-sectional study was conducted among 431 institutionalized male drug users from five selected rehabilitation centers in Sri Lanka. An interviewer-administered questionnaire was used for data collection. The history of exposure to vulnerable factors was assessed using a series of questions based on existing evidence. Chi-square test was used to identify factors associated with exposure to vulnerable factors for drug use at 0.05 significance level. Results: Experimental usage, peer pressure, being unaware about harmful outcomes of drug use, ability to conceal drug use behavior from family, easy accessibility, previous use of alcohol and tobacco, history of exposure to psychoactive substance use within the usual living set up, being in a family with inadequate protection and an unsatisfactory parenting status were identified as common characteristics of people with illicit drug use disorders and drug use behavior. The age of the first drug use was positively correlated with the age of the first alcohol use (r = 0.687; P < 0.01) and first smoking (r = 0.732; P < 0.01). Ethnicity, area of residence, severity of drug use, and age of initiation of drug use had statistically significant association with exposure to vulnerable factors for drug use (P < 0.05 for all). Conclusion: Characteristics of people with illicit drug use disorders and drug use behavior were varied while the history of exposure to vulnerable factors for drug use was not uncommon in the sample. The study recommends considering these study findings during designing appropriate preventive and harm reduction strategies for illicit drug use.